Discourse markers in TV interviews: A corpus-based comparative study of Chinese and the western media - Fu, Yanli; Ho, Victor (Frontiers in Psychology, 2022)
This paper, which is part of an on-going large-scale study, quantitatively explores and compares the frequency, patterns, and positions of the three most frequently used discourse markers (DMs): so, and, but in TV interviews. The data comprises three corpora consisting of three media programs from China, the US, and the UK. Results show that there is a statistically significant difference in the frequency of the DM so and the DM and, with each DM having the highest frequency in a specific corpus. Four co-occurring strings (and so, and but, so but, but so) are identified in the three corpora with the DM co-occurrence “and so” having the highest frequency in the American program, supporting the claim that this combination is a typical use in American English. The general positional distribution of the three DMs is similar with the highest tendency in the initial position, which can be attributed to the program’s interactivity. The findings will enhance our understanding of the three DMs used in media discourse and should be of practical significance to media hosts and guests in achieving a better bilateral communication.